2020
DOI: 10.1039/d0cy01137a
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic oxidation of NH3over noble metal-based catalysts: state of the art and future prospects

Abstract: Selective catalytic oxidation of ammonia into nitrogen and water vapor (NH3-SCO) is considered to be an efficient technique to eliminate the hazardous and pungent gaseous phase NH3, which mainly emitted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 152 publications
1
95
0
Order By: Relevance
“…The H 2 N–H⋯O hydrogen bond formed in the intermediate structure facilitates the first ammonia oxidative deprotonation step, similar to what was observed for catalytic ammonia oxidation on metal oxide surfaces. 61,62 Thus formed *NH 2 species obtained in this spontaneous process replace *OH and form a bridge structure as was shown in the recent DFT work. 50 Subsequently, *NH 2 undergoes two spontaneous deprotonation steps with a loss of one electron at each step to form *NH and then *N species.…”
Section: Resultssupporting
confidence: 66%
“…The H 2 N–H⋯O hydrogen bond formed in the intermediate structure facilitates the first ammonia oxidative deprotonation step, similar to what was observed for catalytic ammonia oxidation on metal oxide surfaces. 61,62 Thus formed *NH 2 species obtained in this spontaneous process replace *OH and form a bridge structure as was shown in the recent DFT work. 50 Subsequently, *NH 2 undergoes two spontaneous deprotonation steps with a loss of one electron at each step to form *NH and then *N species.…”
Section: Resultssupporting
confidence: 66%
“…The Pt/TiO2 systems are less investigated for this reaction than the traditionally used Pt/Al2O3. 29,30 However, unlike the Pt/Al2O3 catalysts, for the Pt/TiO2 system, there is a possibility of the metal-support interaction, which can influence the catalytic properties. [31][32][33][34][35][36] It was shown that the metal-support interaction can provide stabilization of the metal platinum particles.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] The NH 3 -SCO is the most promising method for the depletion of ammonia that is recognized as one of the main emerging atmospheric contaminants with detrimental effects on the environment and human health. [25][26] The interest in this process is increasing in the last years, motivated by the release of ammonia to the atmosphere originated by slip from the selective catalytic reduction of NO x (NH 3 -SCR-NO x ) and more restricting regulations in gas emissions. The SCR units are fitted in heavy-duty diesel vehicles and power plants for the removal of NO x and use as reducing agent an excess of on-board generated ammonia from urea.…”
Section: Introductionmentioning
confidence: 99%